Association between Hospital volume of cardiopulmonary resuscitation for in-hospital cardiac arrest and survival to Hospital discharge. (1st March 2020) - Akintoye, Emmanuel; Adegbala, Oluwole; Egbe, Alexander; Olawusi, Emmanuel; Afonso, Luis; Briasoulis, Alexandros
Abstract: Background: Prior studies have shown that hospital case volume is not associated with survival in patients with out-of-hospital cardiac arrest (OHCA). However, how case volume impact on survival for in-hospital cardiac arrest (IHCA) is unknown. Methods: We queried the National Inpatient Sample (NIS) in the U.S. 2005–2011 to identify cases in which in-hospital CPR was performed for IHCA. Restricted cubic spine was used to evaluate the association between hospital annual CPR volume and survival to hospital discharge. Results: Across more than 1000 hospitals in NIS, we identified 125, 082 cases (mean age 67, 45% female) of IHCA for which CPR was performed over the study period. Median [Q1, Q3] case volume was 60 [34, 99]. Compared to those in the 1 st quartile of case volume, hospitals in the 4th quartile tends to have younger patients (mean = 66 vs 68 yrs), higher comorbidities (median Elixhauser score = 4 vs 3), and in low income areas (37 vs 30%). Overall, 23% of the patients survived to hospital discharge. There was a non-linear association between CPR volume and survival: a non-significant trend towards better survival was observed with increasing annual CPR volume that reached a plateau at 51–55 cases per year, after which survival began to drop and became significantly lower after 75 cases per year (p for non-linearity<0.001). Compared to those in first quartile of case volume, hospitals in 4 th quartile had higher length of stay (median = 8 vs 10 days, respectively) and higher rate of non-routine home discharge (64% vs 67%) among those who survived. Conclusion: Unlike OHCA, low CPR volume is an indicator of good performing hospitals and increasing CPR case volume does not translate to improve survival for IHCA.